2006
DOI: 10.1111/j.1365-2036.2006.03026.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful induction of tolerance to infliximab in patients with Crohn's disease and prior severe infusion reactions

Abstract: SUMMARY AimTo appraise the tolerance and efficacy of an induction of tolerance protocol to infliximab permitting the re-administration of the drug to patients with Crohn's disease having had infusion reactions requiring suspension of treatment. MethodsFourteen patients were included in the induction of tolerance protocol. Each infusion of infliximab (5 mg/kg) was divided into 11 escalating 15 min increments over a 3-h time period. The induction of tolerance procedure was repeated for subsequent infusions. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…This process has been invaluable in allowing the use of life-saving and disease-modifying medications in situations in which there is no acceptable treatment alternative. Desensitization has been described in case reports or small series for rituximab, 27 infliximab, [28][29][30] trastuzumab, 31,32 muronomab, 33 cetuximab, 34 and omalizumab. 12 No desensitizationrelated deaths have been reported.…”
mentioning
confidence: 98%
“…This process has been invaluable in allowing the use of life-saving and disease-modifying medications in situations in which there is no acceptable treatment alternative. Desensitization has been described in case reports or small series for rituximab, 27 infliximab, [28][29][30] trastuzumab, 31,32 muronomab, 33 cetuximab, 34 and omalizumab. 12 No desensitizationrelated deaths have been reported.…”
mentioning
confidence: 98%
“…In 2006, Duburque et al reported their experience with desensitization in 14 patients with Crohn's disease who had developed infusion reactions despite prophylactic administration of hydro cortisone [17]. The protocol was specifically for patients with severe infusion reactions for whom the continuation of infliximab therapy was considered as the only therapeutic option.…”
Section: Infliximabmentioning
confidence: 99%
“…Initially, Puchner et al [14] published in 2001 a successful induction of tolerance to IFX in 2 cases including a child, with prior anaphylactic reaction. Later, Duburque et al [15], Mourad et al [17], and Brennan et al [16] reported the successful induction of tolerance to IFX in, respectively, 10, 12, and 6 patients with CD and various other autoimmune diseases. More recently, a study evaluating the impact of IgE antibodies detection in the management of IFX retreatment showed an efficient induction of tolerance in 3 out of 4 patients [13].…”
Section: Discussionmentioning
confidence: 99%